High‐Resolution Three‐Dimensional Imaging of Individual Astrocytes Using Confocal Microscopy. Issue 1 (18th February 2020) - Testen, Anze; Kim, Ronald; Reissner, Kathryn J.
Abstract: Astrocytes play numerous vital roles in the central nervous system. Accordingly, it is of merit to identify structural and functional properties of astrocytes in both health and disease. The majority of studies examining the morphology of astrocytes have employed immunoassays for markers such as glial fibrillary acidic protein, which are insufficient to encapsulate the considerable structural complexity of these cells. Herein, we describe a method utilizing a commercially available and validated, genetically encoded membrane‐associated fluorescent marker of astrocytes, AAV5‐GfaABC1D‐Lck‐GFP. This tool and approach allow for visualization of a single isolated astrocyte in its entirety, including fine peripheral processes. Astrocytes are imaged using confocal microscopy and reconstructed in three dimensions to obtain detailed morphometric data. We further provide an immunohistochemistry procedure to assess colocalization of isolated astrocytes with synaptic markers throughout the z‐plane. This technique, which can be utilized via a standard laboratory confocal microscope and Imaris software, allows for detailed analysis of the morphology and synaptic colocalization of astrocytes in fixed tissue. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Microinjection of AAV5‐GfaABC1D‐Lck‐GFP into the nucleus accumbens of rats Basic Protocol 2 : Tissue processing and immunohistochemistry for post‐synaptic density‐95 Basic Protocol 3 : Single‐cell image acquisition Basic Protocol 4 : Three‐dimensional reconstruction of single cells Basic Protocol 5 : Three‐dimensional colocalization analysis